Occurrence of Intersex in the Marine Mussel Perumytilus purpuratus (Mollusca: Bivalvia): Does Gonadal Parasitism Play a Role? - Pablo A. Oyarzún; Sebastián Diaz; Sara M. Rodríguez; Gonzalo Ruiz-Tagle; José J. Nuñez; Jorge E. Toro (Biology)
Intersexuality is a reproductive phenomenon that occurs in some gonochoric species and refers to the simultaneous presence of both male and female gametes within the same individual. Although this phenomenon has been reported in various invertebrate species, many aspects remain poorly understood, especially in marine mussels. However, it has been suggested that the prevalence of parasites within populations could induce the occurrence of intersex animals. We studied intersexuality in the marine mollusk Perumytilus purpuratus, a key species of the rocky intertidal zone on the southeastern coast of the Pacific Ocean. A total of 6472 mussels from eight locations in northern and southern Chile were analyzed. We estimated the size of the specimens, the sex ratio of the population, and the prevalence of parasites. Additionally, we examined the germ cells of intersex mussels. The results showed that the male-to-female sex ratio (1:1) was maintained in the populations. Intersex mussels were found in six of the eight locations, representing 0.19% of the mussels analyzed. However, no parasites were found in the intersex animals. Additionally, the abundance of intersex individuals was not correlated with parasitism levels in the population. In intersex mussels, the gonadal tissue was compartmentalized, with male and female germ cells remaining separate. It is concluded that intersexuality in Perumytilus purpuratus is a low-frequency reproductive phenomenon, likely resulting from an alteration in the sex determination mechanism. Intersexuality offers a valuable opportunity to explore the biological aspects of sex determination in mussels. Therefore, further research in this area should be pursued.